The Jan Laski Society of Lovers of the History of Polish Reformation in Vilnius (1918–1939) – Genesis, Legal Structure and Activity - Dąbrowski, Przemysław (Odrodzenie i Reformacja w Polsce, 2018)
The Jan Laski Society of Lovers of The History of Polish Reformation in Vilnius, established in 1916, played a significant role in the propagation of history of the Reformation in Polish lands. It owed its achievements to the intensive efforts of its members who organized numerous meetings and lectures and published books on the Evangelical-Reformed Church and the influence the Reformation had on national culture and language. Towards the end of its existence the Society doubled the number of its members, which clearly shows that it was growing in prestige and popularity.